Status of Vitamin D among Patients Visiting a Tertiary Care Centre in Rupandehi, Nepal - Shah, Tirtha Narayan; Sinha, Amar Kumar; Jha, Krishna Kumar; Prasad, Ram Jiban (International Journal of Applied Sciences and Biotechnology, 2021)
Serum vitamin D is one of the fat-soluble vitamin which has the role in maintenance of calcium and phosphorus levels and ultimately proper bone health and various physiological processes. Although many studies prevail hypovitaminosis D, we focused to find out the pattern of elevated or decreased serum vitamin D level as its deficiency and surplus have adverse effects to our health.. For this, a retrospective study was done from the records present in a hospital laboratory of Devdaha Medical College and Research Institute (DMCRI), Rupandehi, Nepal from January 2018 to December 2020 where 201 participants with 70.1% male and 29.9% female with different age groups were present. From total participants, 14.9% had deficient, 42.8% had insufficient, 35.3% had sufficient and 7% had high level of serum vitamin D. Male had 2.9% deficient and 14,9% insufficient vitamin D whereas female had 11.9% deficient, 27.8% insufficient and 7.0% surplus vitamin D. The greater prevalence of hypovitaminosis D in the females than the males could be overcome by the necessary strategies in the form of further studies and judicious supplementation vitamin D in the target population by monitoring the level of serum vitamin D. Int. J. Appl. Sci. Biotechnol. Vol 9(4): 256-260.